Absorption and plasmon resonance of Bi-metallic core-shell nanoparticles on a dielectric substrate near an external tip. (January 2020) - Avşar, Dilan; Ertürk, Hakan; Mengüç, M. Pınar
Highlights: Plasmonic responses of core-shell nanoparticles on a substrate are investigated. Bimetallic pairs are considered for absorption enhancement and sensing. Near-field coupling between the nanoparticle and AFM tip investigated. Dielectric transition of AFM tip materials is analyzed for the absorption mechanism. DDA-SI-v is used for calculating the interactions with an evanescent wave. Abstract: Absorption efficiency profiles and localized surface plasmon resonance (LSPR) wavelengths are reported for metallic core-shell nanoparticles (NPs) placed over a BK7 glass substrate. A numerical study is performed with the vectorized version of the discrete dipole approximation with surface interactions (DDA-SI-v). Gold (Au) and silver (Ag) metallic components are used for the simulations of two different core-shell structures. Absorption enhancement and the hybrid modes of plasmon resonances of the core-shell structures are compared by using a measure that defines a size configuration. It is observed that a small volume fraction of the core sizes results in shell domination over the plasmon response. An additional study is conducted to discern the sensitivity of the refractive index of nanoparticles in different surrounding environments. With a selected core-shell size configuration of Ag-Au pairs, a significant absorption enhancement with a redshift of LSPR wavelength is observed for both Ag core-Au shell and Au core-Ag shell NPs. The absorption behavior of the bare metallic NPs and selected core-shell pairs in proximity to an external probe's tip is also analyzed. The gallium phosphide (GaP) and silicon (Si) tip usage are investigated with transverse electric (TE) and transverse magnetic (TM) wave polarizations. It is observed that the dominance of light polarization on the absorption enhancement of the NPs switches at different wavelengths, where the dielectric transition for tip materials occurs. These findings show the possible targeted uses of metallic core-shell nanoparticles in several areas such as nanomanufacturing, localized heating, bio-sensing, and material detection applications.